MANAGEMENT OF NEURODERMATITIS ON THE ELDERLY IN KOTA KARANG VILLAGE - Listiandoko, Raden Dicky Wirawan (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Neurodermatitis circumscripta is a chronic severely pruritus disorder characterized by one or more lichenified plaques in which the skin is thickened and there are accentuated skin marking resembles tree bark. There are four steps treatment for neurodermatitis circumscripta, which are identifying underlying disease improve barrier layer function; reduce inflamation and break up the it scratch cycle; identification of internal and external factors as ethiology of neurodermatitis circumscripta; and the therapy for neurodermatitis circumscripta. Descriptive analyzes with primary data obtained through anamnesis, physical examination, and home visits for family assessment. Secondary data were obtained from medical records. Management of health problem using family medicine approach which are hollistic, comprehensive, integrated, and continous. Patient and member of the family understand more about neurodermatitis circumscripta and family participation, but intervention has not been done optimally because limitation of time. Clinical and psychosocial problems are complex and need a long time collaboration between healthcare providers and family for its management. Health providers do not only solve patient’s health problem but also give education to the family about health problem and how family support is very important for the management. [J Agromed Unila 2014; 1(2):139-144] Keywords: family medicine, neurodermatitis circumscripta